Project Competency and Performance Recovery (CPR) and Students’ Level of Performance in Technology and Livelihood Education - Sublay, Evelyn (JPAIR Institutional Research, 2024)
This study aimed to investigate the effectiveness of Project Competency and Performance Recovery (CPR) using quantitative research, specifically the one-group pretest-post-test design. The research study was conducted in Palo Alto Integrated School, where one-hundred twenty (120) respondents were included from Grades 7 – 10, respectively. The mean, standard deviation and paired t-test were used to examine the results of the learners’ academic performance from the second quarter and third quarter. The study’s findings revealed that at the reopening of classes, the mean academic performance of learners from grades 7 – 10 was at the ’developing’ stage. This was before the implementation of Project CPR. On the other hand, after the implementation, there was a slight improvement in the learners’ mean academic performance, particularly from grades 8 and 10, which improved from “developing” to “Approaching Proficiency”. Only grade 7 learners have not improved after the implementation of the project since it is statistically evident that there is no significant difference between the results of the second quarter and the third quarter’s performance. Moreover, findings also show that Project CPR was effective in recovering learning losses. The data for the test of significant difference between the second and third quarters revealed a significant difference, particularly from grades 8, 9, and 10. The study’s conclusive findings will serve as the foundation for replication with a larger sample size and a broader focus.